Soil erodibility and quality of volcanic soils as affected by pine plantations in degraded rangelands of NW Patagonia - La Manna, Ludmila Andrea (2016)
NW Patagonia in Argentina has high potential for planting fast-growing exotic conifers, supported by its volcanic soils. Nonetheless, many aspects related to the effects of pine plantations on soil are still unknown. We aimed to evaluate the quality and erodibility of volcanic soils under the hypothesis that Pinus ponderosa plantations increase the quality and decrease the erosion rate of soils compared to degraded rangelands. Rainfall simulation experiments were performed in degraded rangeland soils and in pine plantations with none, partial and complete removal of fresh litter and duff layers. Results showed that rangeland soils were highly susceptible to water erosion. Sediment production in the rangeland varied between 144 and 750 g m−2. Loamy sand soils, poor in organic matter (OM) and without non-crystalline aluminosilicates, were the most erodible soils. The plantations improved soil quality, with positive changes in OM content and total and effective porosity, mainly in soils without non-crystalline materials. Soil erosion in pine plantations was negligible when fresh litter was either conserved or removed, with erosion rates as low as 6.2 ± 1.5 and 23.7 ± 7.9 g m−2, respectively. Even when fresh litter and duff layers were totally removed, soil erosion rates in the pine plantations (129.1 ± 23.2 g m−2) were lower than in the rangeland sites; however, this reduction was significant only for the most erodible soils. The high erodibility of volcanic soils and the low soil cover in overgrazed rangelands revealed the fragility of the soils in the study area. We show that pine plantations, an alternative land use of rangelands, improve some aspects of soil quality, provide a mulching effect through the litter layer and became a mean for controlling soil erosion.